(untitled) (Archives of Criminology, 2023)
The European Union is empowered to legislate in criminal matters; the European Parliament and the Council may establish minimum rules, in certain areas, concerning the definitions of criminal offences and sanctions or facilitating cross-border cooperation. However, in the field of asset confiscation, the EU authorities seem to go beyond these competences in their legislative activity. In this paper the author refers to this and other problems of EU legislation in criminal matters: covering up the insufficient competence to legislate with the argument of needing harmonisation, the lack of reliable data that would justify EU legislative activity and the problematic concept of effectiveness in EU legislation.